2020
DOI: 10.1109/access.2020.2994026
|View full text |Cite
|
Sign up to set email alerts
|

A Reliability Approach to Development of Rollover Prediction for Heavy Vehicles Based on SVM Empirical Model With Multiple Observed Variables

Abstract: The rapid development of cooperative vehicle-infrastructure system (CVIS) improves the communication reliability between vehicles and road environment. These communications enable the accurate vehicle rollover prediction in Human-Vehicle-Road interaction. However, considering the strong nonlinear characteristics of Human-Vehicle-Road interaction and the uncertainty of modeling, the traditional deterministic method cannot meet the requirement of accurate prediction of rollover hazard for heavy vehicles. In orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…On the other hand, scholars have developed a simple point–mass model, transient BICYCLE model [ 9 ], and more complex multibody model [ 10 ] to describe the motion states and dynamics of vehicles. The lateral stability of passenger cars, SUVs, and trucks based on the SSF [ 11 ], lateral load transfer ratio [ 12 , 13 ], and friction margin [ 14 ], has also been studied extensively. Furthermore, it was found that the center of gravity, tire characteristics, and suspension systems of SUVs mean that their lateral stability is not as good as that of passenger cars [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, scholars have developed a simple point–mass model, transient BICYCLE model [ 9 ], and more complex multibody model [ 10 ] to describe the motion states and dynamics of vehicles. The lateral stability of passenger cars, SUVs, and trucks based on the SSF [ 11 ], lateral load transfer ratio [ 12 , 13 ], and friction margin [ 14 ], has also been studied extensively. Furthermore, it was found that the center of gravity, tire characteristics, and suspension systems of SUVs mean that their lateral stability is not as good as that of passenger cars [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rollover can be warned using several methods to predict it. Zhu et al introduced a new predictive model called the SVM (Support Vector Machine) Empirical Model in [ 10 ], and the accuracy of this model ranges from 70 ÷ 100%. This is a new approach, and it is quite complicated.…”
Section: Introductionmentioning
confidence: 99%
“…This is a new approach, and it is quite complicated. According to the diagram of the algorithm (Fig 3 in [ 10 ]), this model has no feedback from the output. Vehicle rollover can also be predicted utilizing the neural network algorithm introduced by Sanchez et al in [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The essence of this model is to use a support vector machine (SVM) algorithm. This algorithm is also applied to the heavy truck model with multiple observed variables, according to Zhu et al [20,21]. An algorithm to predict car rollover that uses contour lines of RI is introduced by Zhang et al in [22].…”
Section: Introductionmentioning
confidence: 99%